The effect of liquid foliar fertilizer and pruning combinations on the growth of productive phase arabica coffee plants (Coffea arabica L.) - Putri, Syifa Djuita; Balapradhana, Alvito Krishna; Ariyanti, Mira; Anjarsari, Intan Ratna Dewi; Maxiselly, Yudithia (Universitas Padjadjaran, 2026)
In recent years, productivity decline in arabica coffee has become a real issue in Indonesia. This decay has been brought about by various external and internal factors that are beyond human control. Various factors, including suboptimal cultivation practices, take part in this process. The objective of the present study was to evaluate the effect of pruning combined with foliar fertilizer application (coconut water and sugarcane molasses) and 6-benzylaminopurine (BAP) on the vegetative growth of arabica coffee plants during the production phase. The research was conducted at Ciparanje Experimental Field, Universitas Padjadjaran, using a randomized complete block design with seven treatments including a control (without pruning and foliar application), application of coconut water (75%, 750 mL L⁻¹), sugarcane molasses (2 mL L⁻¹), and BAP at 60 ppm, each applied with and without pruning, and four replications. In this research, the main parameters observed included the number and length of the lateral branches, leaf chlorophyll index, leaf area, canopy width, number of fruit clusters per branch and per tree, and coffee cherry fruit weight. It emerged that the combination of pruning and the use of sugarcane molasses at 2 ml/L significantly increased lateral branch formation, leaf area, and the number of fruit clusters per tree. The integration of pruning with foliar treatments effectively supported optimal growth of productive-phase arabica coffee plants.